Distinct microbial populations are tightly linked to the profile of dissolved iron in the methanic sediments of the Helgoland mud area, North Sea - Oni, Oluwatobi E.; Miyatake, Tetsuro; Kasten, Sabine; Richter-Heitmann, Tim; Fischer, David; Wagenknecht, Laura; Ksenofontov, Vadim; Kulkarni, Ajinkya; Blumers, Mathias; Shylin, Sergii; Costa, Benilde; Klingelhöfer, Göstar; et al. (Frontiers in Microbiology, 2015)
Iron reduction in subseafloor sulfate-depleted and methane-rich marine sediments is currently a subject of interest in subsurface geomicrobiology. While iron reduction and microorganisms involved have been well studied in marine surface sediments, little is known about microorganisms responsible for iron reduction in deep methanic sediments. Here, we used quantitative PCR (Q-PCR)-based 16S rRNA gene copy numbers and pyrosequencing-based relative abundances of bacteria and archaea to investigate covariance between distinct microbial populations and specific geochemical profiles in the top 5 m of sediment cores from the Helgoland mud area, North Sea. We found that gene copy numbers of bacteria and archaea were specifically higher around the peak of dissolved iron in the methanic zone (250-350 cm). The higher copy numbers at these depths were also reflected by the relative sequence abundances of members of the candidate division JS1, methanogenic and Methanohalobium/ANME-3 related archaea. The distribution of these populations was strongly correlated to the profile of pore-water Fe2+ while that of Desulfobacteraceae corresponded to the pore-water sulfate profile. Furthermore, specific JS1 populations also strongly co-varied with the distribution of Methanosaetaceae in the methanic zone. Our data suggest that the interplay among JS1 bacteria, methanogenic archaea and Methanohalobium/ANME-3-related archaea may be important for iron reduction and methane cycling in deep methanic sediments of the Helgoland mud area and perhaps in other methane-rich depositional environments.